Outcomes of Primary Surgical Cytoreduction in Patients with BRCA-associated High-grade Serous Ovarian Carcinoma - Hyman, David M. (2012)
OBJECTIVE: BRCA-associated and sporadic ovarian cancers have different pathologic and clinical features. Our goal was to determine if BRCA mutation status is an independent predictor of residual tumor volume following primary surgical cytoreduction. METHODS: We conducted a retrospective analysis of patients with FIGO stage IIIC-IV high-grade serous ovarian cancer classified for the presence or absence of germline BRCA mutations. The primary outcome was tumor-debulking status categorized as complete gross resection (0mm), optimal but visible disease (1-10mm), or suboptimal debulking (>10mm) following primary surgical cytoreduction. Overall survival by residual tumor size and BRCA status was also assessed as a secondary endpoint. RESULTS: Data from 367 patients (69 BRCA mutated, 298 BRCA wild-type) were analyzed. Rate of optimal tumor debulking (0-10mm) in BRCA wild-type and BRCA-mutated patients were 70.1% and 84.1%, respectively (P=0.02). On univariate analysis, increasing age (10-year OR, 1.33; 95% CI, 1.07–1.65; P=0.01) and wild-type BRCA status (OR, 0.47; 95% CI, 0.23–0.94, P=0.03) were both significantly associated with suboptimal surgical outcome. On multivariate analysis, BRCA mutation status was no longer associated with residual tumor volume (OR, 0.63; 95% CI, 0.31–1.29; P=0.21) while age remained a borderline significant predictor (10-year OR, 1.25; 95% CI,1.01–1.56; P=0.05). Both smaller residual tumor volume and mutant BRCA status were significantly associated with improved overall survival. CONCLUSION: BRCA mutation status is not associated with the rate of optimal tumor debulking at primary surgery after accounting for differences in patient age. Improved survival of BRCA carriers is not the result of better surgical outcomes but instead intrinsic tumor biology.